Analysis Of Optimum Inventory Of Rice Milling Businesses In Konawe District - Hasniati Hasniati (Program Studi Agroteknologi Fakultas Pertanian Universitas Dayanu Ikhsanuddin, 2019)
Konawe Regency is the center of rice production, so the businesses engaged in rice milling develop quite a lot. Data for 2018 shows that the number of rice mills with a large capacity in Konawe Regency reaches 209 units. Increasing the number of milling businesses in Konawe Regency because it is supported by a land area of ​​57,519 hectares of paddy rice fields with a production of 53,976 tons (Distan Konawe Regency, 2018). Besides this potential, it is also supported by rice production from other districts, namely East Kolaka Regency. Kolaka Regency. And Konsel District. This situation has the potential for competition in obtaining grain as raw material, which is quite strict so that an in-depth analysis is needed in determining the optimal inventory of the grain milling company. The purpose of the research is to examine the process of procurement of raw materials for grain and analyze how much is the optimal inventory so that the grain milling company gets maximum profit. Research variables include data on engine capacity, the average number of milled rice per day, fuel consumption, and other costs. The data is analyzed by economy order quantity (EOQ). The research result that leads k kan p roses procurement of raw materials made in 29 sub-districts spread over four districts in the region of Southeast Sulawesi Proponsi as much as 11 948 tonnes. The optimal inventory so that the company can get the maximum profit is 8,398 tons per year, while the actual inventory is 7,170 tons per year.